Tbet promotes CXCR6 expression in immature natural killer cells and natural killer cell egress from the bone marrow - Cuff, Antonia O. (Immunology, 2020)
Tbet‐deficient mice have reduced natural killer (NK) cells in blood and spleen, but increased NK cells in bone marrow and lymph nodes, a phenotype that is thought to be the result of defective migration. Here, we revisit the role of Tbet in NK cell bone marrow egress. We definitively show that the accumulation of NK cells in the bone marrow of Tbet‐deficient Tbx21 (−/−) animals occurs because of a migration defect and identify a module of genes, co‐ordinated by Tbet, which affects the localization of NK cells in the bone marrow. Cxcr6 is approximately 125‐fold underexpressed in Tbx21 (−/−), compared with wild‐type, immature NK cells. Immature NK cells accumulate in the bone marrow of CXCR6‐deficient mice, and CXCR6‐deficient progenitors are less able to reconstitute the peripheral NK cell compartment than their wild‐type counterparts. However, the CXCR6 phenotype is largely confined to immature NK cells, whereas the Tbet phenotype is present in both immature and mature NK cells, suggesting that genes identified as being more differentially expressed in mature NK cells, such as S1pr5, Cx3cr1, Sell and Cd69, may be the major drivers of the phenotype.